Investigating STLV-1 infection in African green monkeys: a model for understanding HTLV-1 pathogenesis - Víctor Â. Folgosi; Liliane A. Carneiro; Sabri S. Sanabani; Felipe B. Freitas; Mayara N. S. da Silva; Amanda L. Silva; Gerlane N. Noronha; Ariela S. Farias; Hebert F. Culler; Carlos F. Apoliano; Luciano Lopes; Juliana Pereira; et al. (Frontiers in Medicine, 2025)
IntroductionSimian T-cell leukemia virus type 1 (STLV-1) and human T-lymphotropic virus type 1 (HTLV-1) are homologous viruses with high genetic identity. STLV-1 infections in non-human primates serve as valuable models to study HTLV-1 pathogenesis.MethodsThis study investigated STLV-1 infection in captive green monkeys (Chlorocebus aethiops) in Brazil. Blood samples from 52 animals were collected and analyzed for viral presence, genetic characterization, and pathological manifestations.ResultsSTLV-1 infection was detected in seven animals, corresponding to a seroprevalence of 13.4%. Phylogenetic analysis showed that the STLV-1 strains identified are more closely related to baboon STLV-1 strains and human African HTLV-1 isolates than to other STLV-1 variants, suggesting a shared evolutionary history and possible cross-species transmission. Clinically and hematologically, STLV-1 infection in C. aethiops presented parallels to HTLV-1 infection in humans, including the presence of characteristic “flower cells” and similar lymphoproliferative disorders.DiscussionThese findings reinforce the relevance of C. aethiops as a natural model for studying HTLV-1 infection and pathogenesis. The genetic and clinical similarities indicate potential mechanisms of viral evolution and transmission, providing insights that may aid in understanding HTLV-1-associated diseases in humans.